Brain Anatomy in Latino Farmworkers Exposed to Pesticides and Nicotine. Issue 5 (May 2016) - Laurienti, Paul J.; Burdette, Jonathan H.; Talton, Jennifer; Pope, Carey N.; Summers, Phillip; Walker, Francis O.; Quandt, Sara A.; Lyday, Robert G.; Chen, Haiying; Howard, Timothy D.; Arcury, Thomas A.
Abstract : Objective: Migrant tobacco farmworkers experience regular occupational exposure to pesticides and nicotine. The present study was designed to determine whether there are differences in brain anatomy between Latino farmworkers and non-farmworkers. Methods: Magnetic resonance brain images were compared between farmworkers and non-farmworkers. In addition, blood cholinesterase activity and urinary cotinine levels were also used to identify associations with pesticide and nicotine exposure. Results: Farmworkers had greater gray matter signal in putamen and cerebellum, and lower gray matter signal in frontal and temporal lobes. Urinary cotinine was associated with the observed differences in brain anatomy, but blood cholinesterase activity was not. Conclusions: Nicotine exposure was associated with neuroanatomical differences between Latino farmworkers and non-farmworkers. Future studies are needed to differentiate iron deposition from brain atrophy and to further assess the potential role of nicotine and pesticide exposure. Abstract : Supplemental Digital Content is available in the text